Peningkatan Literasi Media Digital sebagai Strategi Preventif Penyebaran Hoaks di Era Post-Truth - Syifa Tul Haya; Zikri Fachrul Nurhadi; Siti Nor Amalina Ahmad Tajuddin (KOMUNITA: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2026)
The development of digital technology has changed the way information is accessed and disseminated among students, but their ability to think critically in sorting information has not been fully developed, especially in the post-truth era, which is marked by the rampant spread of false information. This community service aims to increase of digital media literacy as a preventive measure against the spread of hoaxes among students. The target partner is class X students of MAN 1 Garut, with a total of 35 people. The method of implementing the service is carried out through several stages (1) Digital media literacy education and training through interactive lectures; (2) participatory discussion about cases that trigger hoaxes; and (3) evaluation to determine changes in knowledge and attitudes through observation, and post-test. The results of the activity show an increase in students understanding of the importance of digital media literacy in helping to recognize hoaxes, assess information, and increase awareness in using digital media wisely and responsibly. This activity proves that increasing digital media literacy makes a significant contribution to developing students critical thinking skills as one of the efforts to prevent the spread of hoaxes in the digital era in the MAN 1 Garut school environment.